Imitation is not always flattery! The consequences of academy schools in England for further education policy. Issue 2 (3rd April 2017) - Ingleby, Ewan; Tummons, Jonathan
Abstract: This article explores the consequences of the introduction of academy schools in England for further education. It is argued that the uncertainty of the remit of academy schools has indirect consequences for further education and that the employability agenda of the sector is challenged by academy schools. This appears to be happening because of years of government neglect of the further education sector in England. The research participants in the article are critical of the employability skills of young people in general and there is criticism of further education as the sector is regarded as not having developed employability skills in young people effectively. The research is based on a funded evaluation of an employability programme introduced into two academy schools in the north-east of England. The article applies the work of the French philosopher Jean Baudrillard by arguing that the academy schools are simulating the further education agenda. In simulation, a model of reality precedes what is real. The uncertainty surrounding the exact purpose of the academy schools appears to enable them to adopt agendas that have been traditionally associated with other sectors of education. This original argument forms the basis of the new knowledge in the article.